CATASTROPHIC GAS HYDRATE GROWTH UNDER SHUT-IN AND COLD START UP CONDITIONS - SUNDRAMOORTHY, JEGA DIVAN (2016)
In oil and gas industry, one of the major problems faced is the formation of gas hydrates that could cause blockages in petroleum transmission lines. The knowledge to describe how gas hydrates could grow catastrophically under shut-in and cold start up conditions are not available. Utilizing a newly designed apparatus, consisting of six units of identical rocking gas hydrate cell, new insights of how capillary actions can be responsible for catastrophic hydrate growth under both shut-in and cold start up conditions with and without a kinetic hydrate inhibitor are presented. Visual observation shows that the hydrate crystal formation at the brine wetted area close to the brine/gas interface initiates capillary-aided catastrophic hydrate growth. Moreover, no mass-transfer restriction of brine towards catastrophic gas hydrate growth is observed. The capillary force may provide a greater driving force to form gas hydrates than the diffusion rate of gasses into the bulk water phase.